2019
DOI: 10.1002/med.21579
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive peptides and proteins as alternative antiplatelet drugs

Abstract: Antiplatelet drugs reduce the risks associated with atherothrombotic events and show various applications in diverse cardiovascular diseases including myocardial infarctions. Efficacy of the current antiplatelet medicines including aspirin, clopidogrel, prasugrel and ticagrelor, and the glycoprotein IIb/IIIa antagonists, are limited due to their increased risks of bleeding, and antiplatelet drug resistance. Hence, it is important to develop new effective antiplatelet drugs, with fewer side‐effects. The vast re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 98 publications
(247 reference statements)
0
11
0
Order By: Relevance
“…1 Thus, platelets play an essential role in physiological hemostasis process, and abnormal platelet aggregation is the pathological basis of thrombosis. Platelet aggregation is caused by the rupture of atherosclerotic plaques or endothelial injury and may lead to acute thrombotic occlusive ischemic events when the blood supply to tissues is insufficient or is interrupted by athrombus, 2 which is the underlying mechanism for stroke and myocardial infarction as well as the leading cause of morbidity and mortality worldwide. 3,4 Antiplatelet drugs are the main agents used to prevent and treat acute thrombotic occlusive ischemic events.…”
Section: Introductionmentioning
confidence: 99%
“…1 Thus, platelets play an essential role in physiological hemostasis process, and abnormal platelet aggregation is the pathological basis of thrombosis. Platelet aggregation is caused by the rupture of atherosclerotic plaques or endothelial injury and may lead to acute thrombotic occlusive ischemic events when the blood supply to tissues is insufficient or is interrupted by athrombus, 2 which is the underlying mechanism for stroke and myocardial infarction as well as the leading cause of morbidity and mortality worldwide. 3,4 Antiplatelet drugs are the main agents used to prevent and treat acute thrombotic occlusive ischemic events.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive peptides from foods such as dairy products, seafood, seaweeds, nuts, cereals, and other natural sources possess antithrombotic properties that may be useful as antiplatelet agents as they seem to interact with multiple platelet activation pathways. These include inhibition of cyclooxygenase-1 (COX-1), inhibition of type-III collagen-induced aggregation, binding to glycoprotein IIb/IIIa, interacting with fibrinogen and its receptor, and affecting thrombin (73,74).…”
Section: Foods and Nutrients With Antithrombotic Propertiesmentioning
confidence: 99%
“…have drawn special attention due to their special biocompatibility and outstanding health benefits. [16][17][18][19][20] Early epidemiological studies have shown that long-term tea consumption can play a preventive and therapeutic role in cardiovascular diseases. 21 Wang et al grouped the population according to the consumption of tea and found that the incidence of coronary heart disease in the group with the highest green tea consumption was significantly lower than that with the lowest tea consumption.…”
Section: Introductionmentioning
confidence: 99%